Immunology and microbiology: how do they affect social cognition and emotion recognition?. (August 2021) - Barcik, Weronika; Chiacchierini, Giulia; Bimpisidis, Zisis; Papaleo, Francesco
Highlights: Microglia and astrocytes can modulate social behavior in mice and humans in a neurodevelopmental-dependent way. Peripheral immune system can influence social behavior in a neurodevelopmental-dependent way. Social interactions promote spread of microbiota and can modulate microglia, astrocytes and immune system activity. Communications between immunology, microbiology and brain might be crucial for socio-cognitive behavior. Abstract : Social interactions profoundly influence animals' life. The quality of social interactions and many everyday life decisions are determined by a proper perception, processing and reaction to others' emotions. Notably, alterations in these social processes characterize a number of neurodevelopmental disorders, including autism spectrum disorders and schizophrenia. Increasing evidences support an implication of immune system vulnerability and inflammatory processes in disparate behavioral functions and the aforementioned neurodevelopmental disorders. In this review, we show a possible unifying view on how immune responses, within and outside the brain, and the communication between the immune system and brain responses might influence emotion recognition and related social responses. In particular, we highlight the importance of combining genetics, immunology and microbiology factors in understanding social behaviors. We underline the importance of better disentangling the whole machinery between brain-immune system interactions to better address the complexity of social processes.